Interlanguage Pragmatic Competence of University Students: An Error Analysis of Apology Speech Act Strategies in Japanese Learners - Haristiani, Nuria; Christinawati, Devy (International Journal of Language Education, 2024)
While acquiring a second language, learners may encounter challenges and difficulties in effectively carrying out verbal communication in the second language. Mastering the apology speech act is a challenge for L2 learners. The objective of this study is to identify the apology strategies utilized by individuals learning the Japanese language, as well as the specific types and underlying causes of errors produced during the execution of apologetic speech acts. The results of this study were gathered via the Discourse Completion Test (DCT), which encompassed a sample of 150 Japanese language learners. The gathered data were further classified using eight semantic formulas based on the research conducted by Haristiani and Sopiyanti (2019), while the various types and sources of error categorization were conducted based on the theories proposed by Corder (1981) and Richards (1975). The results of this study suggest that Japanese learners utilize the same primary strategies in apology speech acts. Furthermore, the study findings indicated that learners at the intermediate level displayed a higher frequency of errors in their speech compared to learners at the beginner levels and pre-intermediate levels, particularly in the strategy of taking responsibility. The main reason for this was primarily a lack of familiarity with the conventions of sentence structures, the proper use of language, and the appropriate use of expressions. The other sources of errors in language learning are likely to be ignoring language rule restrictions, incomplete application of rules, the learner’s false hypothesis, overgeneralization, and language transfer. This study is anticipated to function as a point of reference for research in interlanguage pragmatics, second-language acquisition, and error analysis. Gaining comprehension of the various problems and difficulties encountered when performing the speech act of apology in Japanese can assist both learners and educators in reducing these errors.